(untitled) (Eurasian Journal of Religious Studies, 2017)
This article analyzes the teachings and activities of adherents of non-traditional religious movement «Jehovah’s Witnesses». This article discusses the main features of this religious movement, founded in 1876 in the United States, its negative impact on society, and explains its devastating effect on human consciousness. We give specific examples of that the main participants are young people who failed to adapt to the requirements of the time, lagging behind in spiritual development. The daily increase in the number of Jehovah’s witnesses proved by means of numbers listed in the «Dissemination of Jehovah’s Witnesses in the territory of post-Soviet states and the current status» section. The article also says that this non-traditional movement work in Kazakhstan, poisoning people’s minds and presenting a danger for the future development of the country. From this research, we can learn that the movement of Jehovah’s witnesses destroys the idea of humanity and patriotic feelings, making conscious and responsible for their actions people to be dependent on nod the instructions of a stranger «living robots» and the activists of this movement – one of the most dangerous in our time provocateurs.